Preparation, characterization and controlled-release property of Fe3+ cross-linked hydrogels based on peach gum polysaccharide. (February 2019) - Zhu, Kai; Yu, Da; Chen, Xiaoyuan; Song, Guanglei
Abstract: In this work, a pH-responsive semi-interpenetrating network (semi-IPN) hydrogel consisted of peach gum polysaccharide (PGP) and Auricularia polytricha β -glucans (APP) was developed. Scanning electron microscope and confocal laser scanning microscope showed that PGP-APP hydrogel had a high porous structure with the formation of PGP-APP semi-IPN. Mössbauer and FT-IR spectroscopy revealed that the hydrogels had COO − -Fe 3+ cross-links through bridging and unidentate binding. Moreover, the delivery capability of the hydrogel was studied. The in vitro release of encapsulated Lactobacillus plantarum CICC20264 and Lactobacillus salivarius CICC23174 in simulated gastric fluid was negligible (below 2 log10  cfu/g), while viable cells were progressively increased with the degradation of hydrogels at stimulated intestinal conditions and a complete release was reached up to more than 7 log10  cfu/g after 10.25 h incubation. On account of stable and dense structure, PGP-APP semi-IPN hydrogels had a significant positive effect ( p  < 0.05) on the viability of bacteria under gastrointestinal transition model. These studies indicated the unique properties of PGP based hydrogels and potential application as intestinal targeted delivery systems. Graphical abstract: A Schematic illustration of the fabrication of the PGP hydrogel and PGP-APP semi-IPN hydrogel. Image 1 Highlights: Novel promising pH sensitive Fe 3+ cross-linked peach gum polysaccharide based hydrogel and semi-interpenetrating polymer network(semi-IPN) hydrogel were formed. The negatively charged hydrogels kept a stable structure in the acidic circumstances and degraded gradually at pH 7.0. Hydrogels system provided a good protection for the probiotic Lactobacillus salivarius CICC23174 and Lactobacillus plantarum CICC20264.